GFDD4-1 Gene Expression in Physcomitrella patens and Homologous Gene in Arabidopsis thaliana in Response to Abiotic Stress - DIAH RATNADEWI; WOLFGANG FRANK (HAYATI Journal of Biosciences, 2005)
A number of abiotic stress responsive genes have been identified from various plant species through reverse genetic strategy. A group of genes are involved in plant responses to stress; they are activated by diverse stress conditions and through different mechanisms. One single gene can be induced by several different stress factors; on the other hand, a number of genes can be up-regulated by a single factor. In Physcomitrella patens, through Northern hybridization, the transcript level of the gene GFDD4-I was detected to be markedly increased by ABA, dehydration and cold, but not by salinity and osmotic stress. In Arabidopsis thaliana, a homologous gene to GFDD4-1 namely At2g47770, was confirmed to fulfill similar function as in P. patens: it is inducible by various abiotic stress treatments, i.e. ABA, dehydration, salinity, and cold. Inducible genes in response to abiotic stress factors may be responsible for plant tolerance to those factors.